Comment: Introducing Artificial Intelligence and the Practice of Neurology in 2035. (8th February 2022) - Jones, Lyell K.; Gross, Robert A.
Abstract : Among the many promises of how technology will change the practice of neurology by 2035, the advanced analytic tools collectively known as artificial intelligence arguably come with the most uncertainties and anxieties. To what extent will machine learning replace the neurologist's role in diagnosis and management? What are the risks of reliance on inscrutable "black box" software that informs our decisions, potentially introducing unseen errors or biases?